Peran Kepala Sekolah Sebagai Penguatan Kapasitas Guru dalam Meningkatkan Mutu Pendidikan - arif ismunandar (Universitas Muhammadiyah Lampung, 2023)
The principal as an educational leader in an educational institution must seek initiatives for quality as a form of effort to build an educational system in his school. As the highest leader in the school, the principal has three main functions, namely as an administrator, supervisor, and educational leader. The principal functions as an educational administrator means that to improve the quality of his school, a principal can improve and develop his school facilities such as buildings, equipment or equipment and others that are covered in the field of educational administration. The presentation of this paper is based on the analysis of library data with a descriptive analysis model. From the results of the discussion, it can be concluded that it reveals the importance of a principal in improving teacher performance in schools. To realize a conducive work climate and a comfortable working atmosphere, cooperation from various parties is needed. In general, a principal as a leader is a principal who has special characters or characteristics that include personality, basic skills, experience and professional knowledge, professional training and skills, administrative knowledge and supervision.Keywords: Principal, Teacher, Education Quality